The Actor from Stanislavski’s Psychology and Boal’s Social Interventioneeling - Jiménez, Pamela (2021)
It is proposed to establish a comparative analysis of the actor’s vision from Stanislavski’s Memory of Emotions and Boal’s Theater of the Oppressed; both have proposed theories that have become role models, in terms of their theatrical theoretical corpus and their way of seeing and experiencing contemporary theater. They have transcended their disciplines, allowing to establish a dialogue between psychology, pedagogy through social intervention and art. The two offered the idea of a new actor, who allows himself to be explored and shared on the scene because he works with and for the human being. They have created the possibility for the viewer to achieve a cathartic process or to exercise a possible modification of the real world; that he dwells lives that are not his or that he provokes an active reaction on his surroundings.